2022
DOI: 10.1111/ans.17967
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of costal cartilage allografts

Abstract: Background: Human costal cartilage remains widely used in the reconstruction of soft tissues, particularly within the field of plastic and orthopaedic surgery. The biologic expense of using autologous human costal cartilage has become superseded by the increasingly common use of irradiated costal cartilage allografts. To date, there has been no histologic investigation of such costal cartilage allografts. This study aims to characterize the histologic variations that exist between different costal cartilage sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[12][13][14] For this reason, in addition to the elimination of donor site morbidity and biologic expense associated with autologous cartilage harvesting, the use of CCC has gained popularity in the field of plastic surgery. 15 Our preliminary experience has shown short-term maintenance of cartilage integrity on clinical assessment along with excellent overall tolerance of CCC evidenced by potential repopulation of lacuna with cells and restoration of aggrecan production on histology. These findings, along with positive longitudinal data from the nasal reconstruction literature, suggest that CCC may have a lower likelihood of resorption than the allogeneic cartilage used in the past.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[12][13][14] For this reason, in addition to the elimination of donor site morbidity and biologic expense associated with autologous cartilage harvesting, the use of CCC has gained popularity in the field of plastic surgery. 15 Our preliminary experience has shown short-term maintenance of cartilage integrity on clinical assessment along with excellent overall tolerance of CCC evidenced by potential repopulation of lacuna with cells and restoration of aggrecan production on histology. These findings, along with positive longitudinal data from the nasal reconstruction literature, suggest that CCC may have a lower likelihood of resorption than the allogeneic cartilage used in the past.…”
Section: Discussionmentioning
confidence: 88%
“…In studies exploring the safety of CCC grafts in rhinoplasty, when comparing the use of autologous grafts to cadaveric cartilage grafts, the findings demonstrated no significant difference in complications, such as resorption, warping, extrusion, contour irregularity, and infection, between the 2 groups 12–14 . For this reason, in addition to the elimination of donor site morbidity and biologic expense associated with autologous cartilage harvesting, the use of CCC has gained popularity in the field of plastic surgery 15 …”
Section: Discussionmentioning
confidence: 99%
“…This study analyzed ECM organization, cellular size, and cellular density of facial and costal cartilages. Previous studies have indicated that facial and costal cartilages are different from each other through the use of light microscopy 11 . However, through the use of SHG microscopy, we are the first to specifically visualize signal intensity of type II collagen to discern ECM differences between surgical remnant human facial and costal cartilages.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have indicated that facial and costal cartilages are different from each other through the use of light microscopy. 11 However, through the use of SHG microscopy, we are the first to specifically visualize signal intensity of type II collagen to discern ECM differences between surgical remnant human facial and costal cartilages. It is important to note that individual collagen fibrils were not resolved because the size of the fibrils is smaller than the diffraction limit of optical microscopy.…”
Section: Discussionmentioning
confidence: 99%